The efectiveness of the ‘tree-diagram’ method in enhancing students’ descriptive essays / Ab. Aziz Husain - Husain, Ab. Aziz (2009)
The study is experimental in nature. Both the experimental group and the control group comprised 30 respondents who are sixth form students of SMK Rantau Panjang, Kelantan. The experimental group was exposed to the ‘tree-diagram’ writing strategy for a period of one month. This meant a total exposure of sixteen 40-minute period for the duration of the month. Both the groups were subjected to a pre-test at the onset of the experiment and a post-test one month later. A t-test showed that there was a significant difference between the pre-test and the post-test writing marks of the experimental group whereas no significant difference was found in the control group. A similar t-test showed that there was a significant difference in the grammar scores of the experimental group but none for the control group. There was also a significant difference between the pre-test and post-test motivation score of the experimental group. However, a t-test indicated that there was no significant difference in the motivational scores of the males and females at the conclusion at the experimental period.